A Survey on Smart Campus Implementation in Malaysia - Musa, Masitah; Ismail, Mohd Norasri; Md Fudzee, Mohd Farhan (Society of Visual Informatics, 2021)
Universities around the world are actively implementing smart campuses. A smart campus is a campus environment capable of providing efficient technology and infrastructure in providing services to support and improve the teaching process, research, and student experience. It comprises initiatives to better support and enhances the better experience in the teaching and learning process and other services in the campus environment. To successfully implement the initiatives, a framework is required to define the scope of the implementation. Several universities in Malaysia are currently developing initiatives to implement their smart campus. This paper surveyed the literature and resources from universities in Malaysia to identify smart campus initiatives implemented following the smart campus domain. Due to the lack of resources available in the prominent database of indexed journal articles, the main source of review is based on official university sources such as official websites and so on. The result shows that all universities implemented all smart campus domains. Smart Management domain has the highest number of 58% of the overall initiatives. The second highest domain is Smart Learning at 13%, followed by Green Campus at 10%. We also identify that there is new domain of smart campus that was introduced. The new domain is Smart Research. Based on the survey, most universities in Malaysia are actively improving their work processes and the environment by implementing smart campus.